2007
DOI: 10.1002/nbm.1176
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐related and age‐related urinalysis of healthy subjects by NMR‐based metabonomics

Abstract: NMR-based metabonomic analysis is a well-established approach to characterizing healthy and diseased states. The aim of this study was to investigate inter-individual variability in the metabolic urinary profile of a healthy Greek population, not subjected to strict dietary limitations, by NMR-based metabonomics. The overall metabonomic urinalysis showed a homogeneous distribution among the population. The metabolic profile was examined in relation to gender and age, and reference intervals of major metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
139
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(157 citation statements)
references
References 51 publications
18
139
0
Order By: Relevance
“…14 An increased level of hippurate in the urine of diabetic rats indicates an alteration in gut microbiota. Lipid intermediary metabolites, such as choline, betaine and TMAO, are present in the urine, serum and multiple tissues of mice, rats and humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 An increased level of hippurate in the urine of diabetic rats indicates an alteration in gut microbiota. Lipid intermediary metabolites, such as choline, betaine and TMAO, are present in the urine, serum and multiple tissues of mice, rats and humans.…”
Section: Discussionmentioning
confidence: 99%
“…14 Due to its usefulness in evaluating systemic responses to any subtle metabolic perturbation, metabonomics has been used for the diagnosis and evaluation of diabetic patients, 15 and for the identification of potential biomarkers. 16,17 Mäkinen et al has demonstrated that metabonomic analysis is a highly sensitive and specific approach for diagnosing diabetic nephropathy.…”
mentioning
confidence: 99%
“…Hippurate is usually detected in urine and its concentration is related to the microbial activity and composition of the gut (24). An increased level of hippurate in urine samples from diabetic rats indicates an alteration in gut microbiota in the diabetic state.…”
Section: F953mentioning
confidence: 99%
“…NMRbased metabolomics analysis of urine samples that were taken from healthy persons showed that urine was composed of 3-hydroxybutyrate, acetate, succinate, alanine, citrate, creatine, creatinine, dimethylamine, formate, glycine, hippurate, histidine, indoxyl sulfate, lactate, n -acetyl groups from glycoproteins, phenylalanine, taurine, and trimethylamine n -oxide. 34 Our study showed that proliferation and infectivity of parasites were increased in urine-containing medium. Another study reported detection of intracellular metabolites of L. donovani by 1 H NMR spectroscopy, and that Leishmania parasites contained hydroxybutyrate, acetate, lactate, alanine, and succinate, which are also present in urine.…”
Section: Discussionmentioning
confidence: 55%